Positive Periodic Solutions in a Discrete Time Three Species Competition System - Changjin Xu; Yusen Wu (Journal of Applied Mathematics)
A periodic discrete time three species competition system is investigated. With the aid of differential equations with piecewise constant arguments, a discrete analogue of continuous nonautonomous three species competition system is proposed. By using Gaines and Mawhin's continuation theorem of coincidence degree theory, sufficient conditions for the existence of positive periodic solutions of the model are obtained.